Clinical study on the optimal rotational stimulation for the unilateral centrifugation subjective visual vertical test - Zhang, Xueqing; Deng, Qiaomei; Huang, Xiaobang; Wen, Chao; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2025)
ObjectiveTo investigate the optimal stimulation intensity and reference range of the unilateral centrifugation subjective visual vertical (UC-SVV) test and to fill the technical gap in otolithic function evaluation in patients with peripheral vestibular diseases.MethodForty healthy subjects (median age 28 years) underwent a UC-SVV test at rotation speeds of 60, 120, 180, and 240 deg./s using the Neuro Kinetics Inc. (NKI) I-Portal 6.0 NOTC rotating chair system. The deviation angles of the UC-SVV line in the centre and left/right positions at each rotation speed were recorded and analysed.ResultsForty healthy subjects completed the test. The deviation angle of the UC-SVV line differed according to the rotation speed (60, 120, 180, and 240 deg./s). At each rotation speed, the position of the rotation axis (left/centre/right position) affected the deviation angle and direction of the UC-SVV line. At each position of the rotation axis, the rotation speed also affected the deviation angle. When the rotation chair was translated to the left and right positions, the UC-SVV line deviated to the right and left sides, respectively, and the deviation angle increased with increasing rotation speed. The deviation angle at 60 deg./s was significantly less than that at 180 and 240 deg./s (p < 0.001). When the rotation axis was in the centre position, the absolute value of the SVV deviation was less than 0.3, and there was no statistically significant difference at any rotation speed.ConclusionThis study preliminarily discussed the deviation direction and angle of the UC-SVV line under different stimulation intensities in a range of healthy middle-aged subjects. The optimal stimulation intensity for the UC-SVV test is suggested to be 180 or 240 deg./s. Specifically, the peak rotation speed could be 180 deg./s if the subject is unable to tolerate high-speed rotation. This study provides support for improving this technology for evaluation of otolith function and its diagnostic significance in peripheral vestibular diseases.